The Art of Rural Business - Wimmer, Nancy (Archīum Ateneo, 2013)
Grameen Shakti has mastered the art of rural business. Sixteen years ago, the Bangladesh-based renewable energy company was a pioneer in an unexplored market. It had to learn its business from scratch, including how to market solar technology while finding ways to benefit local communities. This would take time, and so Shakti began its business with a plan to become sustainable. The company’s later success—allowing five million people to benefit from light, electricity and additional income— demonstrates what an entrepreneurial approach can achieve in a tough rural environment. It is not magic—what has evolved into a mature business model and is practiced in 1,500 field offices throughout Bangladesh can be studied and learned. It involves financing a low-income clientele, training, reliable service, and above all, innovation and hard work. At its root, Shakti’s business is about making the economy work for everyone, including the people at the bottom of the pyramid